1987
DOI: 10.1111/j.1600-0404.1987.tb03570.x
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic aphasia and dysphoria interpreted as endogenous depression

Abstract: A case is reported of a 29-yr-old female with attacks of aphasia/dysphasia over a period of several months which lasted days to weeks accompanied by a dysphoric state. The patients was for long regarded as endogenous depressive with a hysterical speech disorder. However, the diagnosis of epilepsy was finally made based on generalized attacks, appropriate EEG changes, and the response to anti-epileptic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…This is in accordance with the observation of Ravnik (24), that intravenous administration of diazepam during electric epileptic status during sleep not only suppresses the abnormalities in the EEG, but, moreover, produces an amelioration of the speech disturbances, albeit only temporarily. The analogy with so caIled "epileptic aphasia" (5,11,19,20,22,25,27) is clear, but in the Landau-Kleffner syndrome other cortical functions appear to be involved in the process.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the observation of Ravnik (24), that intravenous administration of diazepam during electric epileptic status during sleep not only suppresses the abnormalities in the EEG, but, moreover, produces an amelioration of the speech disturbances, albeit only temporarily. The analogy with so caIled "epileptic aphasia" (5,11,19,20,22,25,27) is clear, but in the Landau-Kleffner syndrome other cortical functions appear to be involved in the process.…”
Section: Discussionmentioning
confidence: 99%
“…In a group of patients with "conversion motor paralysis" a number of patients displayed aphasic symptomatology, but the lack of linguistic data precludes a further description (Heruti et al, 2002). Only four case studies reported the findings of patients with non-organic language disorders, but in three of them the diagnosis was reconsidered as organic because of the presence of a suspected underlying cause (Linett, 1989;Plesner et al, 1987;Poulin, Macoir, Paquet, Fossard, & Gagnon, 2007). Plesner et al (1987) and Linett (1989) convincingly ascribed the disorders as a consequence of epileptic seizures and stroke respectively.…”
Section: De Letter Et Almentioning
confidence: 94%
“…Only four case studies reported the findings of patients with non-organic language disorders, but in three of them the diagnosis was reconsidered as organic because of the presence of a suspected underlying cause (Linett, 1989;Plesner et al, 1987;Poulin, Macoir, Paquet, Fossard, & Gagnon, 2007). Plesner et al (1987) and Linett (1989) convincingly ascribed the disorders as a consequence of epileptic seizures and stroke respectively. In the case described by Poulin et al (2007), however, the correlation of linguistic alterations with neuro-imaging findings is more doubtful and linguistic evaluation suggests inconsistencies in the patient's performance, which obscures the diagnosis of an organic disorder.…”
Section: De Letter Et Almentioning
confidence: 95%
See 1 more Smart Citation
“…К проявлениям дисфорий могут относиться тревога, тоска, обида, страх, напряженность, злоба, гневливость, агрес-сивность, ипохондричность, настороженность, недове-рие, подозрительность, безысходность, опасения, отчая-ние, подавленное или повышенное настроение, иллюзии, парестезии, сверхценные или бредовые идеи [8]. Дисфо-рии расцениваются разными авторами [2,5,9] как «суб-клинический эпилептический припадок», «психический эквивалент припадка», «импульсивные расстройства на-строения», «измененная реакция организма на судорож-ный приступ», «пароксизмальная субдепрессия», «дисти-мия», «депрессия», «особый вариант сумеречного состоя-ния», «психопатические изменения личности». Отсут-ствие единого подхода к пониманию дисфорических со-стояний определяет противоречивость данных об их рас-пространенности.…”
unclassified